Nursing of two patients with suspected Creutzfeldt-Jakob disease (2例疑似克雅氏病患者的护理) - GENG Yuexiao (耿钥潇); SHI Manyu (史曼玉); MA Jingyi (马靖沂); LI Sha (李沙) (中西医结合护理)
To summarize the nursing experiences of two patients with suspected Creutzfeldt-Jakob disease (CJD). Because of the complex clinical manifestation and rapid course of CD, nurses caring for patients and families are challenged to understand the nature of CJD, manage the patients’ signs and symptoms, and create a therapeutic experience by integrating the psychological, emotional, spiritual, and social components of nursing care. During the hospitalization, nurses had closely observed the changes of patients’ conditions, maintained the patients’ airway unobstructed, strictly executed the disinfection and isolation rules, and carried out the corresponding protection and nursing. Neither patient had any nursing related complications or cross infection during hospitalization. (本文总结2例疑似克雅氏病患者护理的经验。克雅氏病临床表现复杂, 病程进展快速, 临床护士需要了解克雅氏病的本质, 管理患者的症状和体征, 并通过整合护理的心理、情感、精神和社会组成部分来创造治疗经验。在院期间, 应严密观察病情变化, 保持患者呼吸道通畅; 严格执行消毒隔离制度, 做好相应消毒隔离的防护护理。2例患者住院期间未发生护理相关并发症, 未出现交叉感染。)